Motivation and perceived organizational support of adjunct business faculty members teaching face-to-face at a private institution's off campus locations - Ervin, Kathryn A. (Kansas State University, 2018)
As higher education populations are changing, institutions are forced to find new ways to meet students’ needs and schools’ declining budgets. Institutions have found that changing their business models by creating accelerated learning programs and extended campuses are assisting in this area. An outcome of these modifications is increased usage of adjunct faculty. These extended sites typically have small staffs and adjunct faculty members usually have little connection to the main campus, work a primary job, and have limited teaching experience. This research explored adjunct business faculty members teaching face-to-face at a private institution's off campus locations to understand their motivation level and perception of organizational support, as well as if the two interrelate. Multiple regression was completed to further explore the relationship of their demographics and motivation level or perceived organizational support. Self-determination theory was used to explore adjunct faculty members’ motivations, measuring motivation along a continuum from external to intrinsic motivation when a person is not exclusively one or the other. Adjunct faculty members at this institution have an identified motivation level moving toward integration, moving from extrinsic motivation and closer to being more intrinsically motivated. These adjunct faculty members have commitment to the organization’s goals and value their work. Organizational support was used to understand workers’ commitment to their organization as well as their satisfaction. These adjunct faculty members also reported a high level of perceived organizational support. A more thorough understanding of adjunct faculty members’ motivation levels and perceived organizational support will allow for better recruiting as well as create training and development programs to retain qualified, high-quality adjunct faculty members.
Keywords: motivation; percieved organizational support; adjunct faculty; self determination theory; extended campus